Optimalisasi Sumber Daya Pertanian Indonesia untuk Mendukung Program Ketahanan Pangan dan Energi Nasional - Erry Ika Rhofita Rhofita (Jurnal Ketahanan Nasional, 2022)
ABSTRACTAs an agricultural country, Indonesia had abundant natural resources necessary to realized national goals. Natural resources, particularly agriculture, had focused on achieving food resilience  throughout history. At the same time, it could also be used to enhanced the energy resilience  program by utilizing the agricultural residue as a raw material for bioenergy production. Moreover, since 2019, the Covid-19 pandemic had threatened national stability, including food resilience  and the economy. Hence, the Indonesian government decided to developed a food estate program in several provinces through marginal land intensification to produced the food. This study aimed to assessed the agricultural resources' potential to supplied food and energy and its optimization strategies to realized the national defense goals. The research design of this study used descriptive analysis to evaluated the state of agricultural resources. In addition, a resource-focused approach was used to figured out the theoretical potential energy of agricultural residue based on data from each year and the characteristics of crops.The results showed that the amount of energy produced continued to rised  in lockstep with agricultural production and would continue to increased gradually. The annual agricultural waste potential, such as rice residue, had been estimated to generated more than 1300 TJ of energy potential, equivalent to 10 GW of electrical energy. In the future, the sustainability of biomass residue utilization considering environmental, social, and economic factors would support national resilience  programs.